Sorbic Acid as a Wine Preservative-Its Efficacy and Organoleptic Threshold - Tromp, A.; Agenbach, W. A. (South African Journal of Enology and Viticulture, 2017)
Sorbic acid was added to wines in different concentrations to determine its effect on the inhibition of yeasts in semi sweet wines. Sorbic acid proved to be an effective inhibitor of yeast growth when used at a concentration of 200 mg/C in conjunction with a concentration of 100 mg 802/C. As the sorbic acid does not kill the yeast cells but only inhibits them it is imperative that the wine should still be filtered as sterile as possible. Sweet must should not be preserved with sorbic acid because of the danger of bacterial spoilage and the subsequent development of the so-called "geranium" odour in the wines sweetened with infected sweet must. The flavour threshold of sorbic acid itself in dry wines was determined to be between 300 and 400 mg sorbic acid/€. This is virtually double the amount recommended for inhibition, at which concentration no effect should be (nor was) encountered on the quality of the wine.